Factors, effecting on drug bioavailability - P. . Bochkov; R. . Shevchenko; A. . Litvin; G. . Kolyvanov; V. . Zherdev (LLC "Publisher OKI", 2020)
Effects such as excipients, type and general physico-chemical properties of drug form, some of technological manufacturing approaches of the drug forms on bioavailability were consider. Effects of the above-listed factors on the examples used in medical practice were demonstrated.